Power Of Test Path Analysis and Partial Least Square Analysis - Kurniawan, Arif; Loekito, Loekito; Solimun, Solimun (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
Path analysis Analysis and Partial Least Square (PLS) was used to analyze many variables. Both methods use the least squares method (OLS) that can be compared between the two to determine the best method in a study to get an assessment of the behavior of civil servants in the Government of Kediri. The purpose of this study is: comparing path analysis Analysis with Partial Least Square (PLS) on the power of the test and the valueR2.Path method is able to provide the value of R2 higher than Analysis of Partial Least Square (PLS) but the value of the test power analysisi path is smaller than using Analysis of Partial Least Square (PLS). Usage analysis methods Path Analysis and Partial Least Square (PLS) produces behavioral assessment of civil servants in the government of Kediri is nearly equal results and discussion. Based on the analysis to prove that the behavior of civil servants in the Government of Kediri not meet eligibility based on the grade levels and echelons of the civil service